A importância e a influência da fé, da religiosidade e da espiritualidade na experiência da câncer da mama em mulheres mastectomizadas - Santos, Sônia Cristina de Almeida Santana e (2008)
The diagnosis of breast cancer can have undesired and unforeseen repercussions on the life on women s lives, thereby affecting their physical, psychological, social and economic life of women. The treatment process and the notion of living with a fatal disease can trigger a host of negative emotions such as: loss of appetite, insomnia, fear of being forsaken by family and friends and dread of recurrence, in addition to the psychological impact on the feminine body image. This work demonstrates the importance and the meaning that faith, religiosity and spirituality can have in the experience of the diagnosis and treatment of this disease and how these dimensions influenced the quality of life of the women in our sample in this traumatizing period of their lives. Thus faith, religiosity and spirituality have represented the guiding thread that allowed integrating a relevant support of biopsycho- socio-spiritual conditions in the experience of these women